Transcriptional regulation of the virA and virG genes of Agrobacterium tumefaciens. - Winans, S C (1988)
We have used transcriptional and translational fusions between various vir gene promoters and the lacZ gene to study the regulation of vir genes. Like other vir promoters, the virA promoter was induced by acetosyringone in a virA virG-dependent fashion. In addition to being induced by acetosyringone, the virG promoter was partially induced by acidic growth conditions and by starvation for inorganic phosphate. These two conditions appeared to act synergistically. The response to low pH and to phosphate starvation occurred in the absence of the Ti plasmid and must therefore have been mediated by chromosomal genes. Two transposon-generated mutations were obtained which attenuated induction by low pH. One of these transposons was cloned along with flanking DNA; the flanking DNA was sequenced (858 base pairs total), and the predicted amino acid sequence showed homology with a family of proteins including the Rhizobium leguminosarum nodI gene, many of whose members bind ATP and have been implicated in active transport systems. These results are discussed as possible explanations for previous observations that the induction of the octopine vir regulon (i) occurs only in acidic media and (ii) shows hyperbolic kinetics after a long lag phase.